Strategi Perpustakaan dalam Upaya Meningkatkan Kemampuan Bahasa Arab dengan Aplikasi Ipusnas pada Mahasiswa - Niqie, Mohammad Syah Rizal; Miftahuddin, Miftahuddin; Baihaqi, Moh. Hamdan; Rivan, M. (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
The lack of applications that can be provided by libraries to support Arabic language learning is the main background for this research. So the aim of this research is to explore library strategies in improving Arabic language skills among students at Tribakti Islamic University Lirboyo Kediri through the use of applications that can be used by students, IPUSNAS. The IPUSNAS application, which is a digital library service, offers access to various collections of books and materials in Arabic that can support the language learning process. In this context, the strategy implemented includes providing training on application use, as well as utilizing the IPUSNAS application using library facilities. This research uses qualitative methods with data collection techniques through interviews and observation. The research results show that implementing a library strategy based on the IPUSNAS application has significant potential in improving students' Arabic language skills, expanding their access to quality learning resources, and improving their reading skills and understanding of Arabic texts. It is hoped that these findings can contribute to the development of effective digital library models in the context of Arabic language education.